Kehidupan keseharian Komunitas Suku Dayak di Rumah Betang di Desa Ensaid Panjang Kabupaten Sintang Kalimantan Barat - Pether Sobian (Politeknik Negeri Bali, 2021)
This study was conducted to determine the daily lives and social interaction of the Dayak Desa inside and outside Betang Panjai (the long house). This research used a descriptive qualitative approach through the phenomenological method. The study will use semi-structured interviews with three key informants and four other informants. The research data obtained comes from interviews, observation, documentation study and literature study. The theory used in this research is social interaction and social interaction form from Soerjono Soekanto. The results of this study conclude that the Dayak people are active workers, uphold their trust, respect each other and have a high sense of brotherhood. Culture and customs are adhered to in daily practices, including working together in the gardens, fields and rice fields, sharing stories and listening to the conversations of friends and neighbors in the living room. Differences in views on politics, education and technology do not hinder social interaction among residents of Panjang's house.